Income Tax Questions on the CPA Exam: Recent Changes and Future Outlook. - Streuling, G. Fred; Harper, Thomas R. (The Accounting Review, 1973)
The article summarizes the results of a survey on income tax questions included in the 17th Certified Public Accountant (CPA) examinations administered in the U.S. between November 1964 and November 1972. The trend towards testing of conceptual tax knowledge in addition to specific rules and procedures complement the objectives of the Committee on Education and Experience Requirements of the American Institute of CPA, as well as the recommendations of the Committee on Federal Taxation of the American Accounting Association and predecessor committees.